Strategic encounters in innovation and regulation: Healthcare transformation in the era of digital connectivity - Mendonça, S.; Damásio, B.; Santiago, F.; Chen, M.; Santos, A. B.; Cunha, M. P.; Nicita, A. (International Journal of Health Policy and Management, 2022)
Healthcare innovations emerge and develop in institutionally dense selective environments. New projects and propositions in healthcare sectoral ecosystems can be understood as product-service compacts, that is, complex solutions that dynamically integrate tangible and intangible elements in close interaction with users’ needs and the evolving regulatory context under uncertainty and ambiguity. We advance the concept of “strategic encounters” to encapsulate, capitalise and extend the contribution by Palm and Fischier’s on the key enabling managerial factors for healthcare innovation implementation under conditions of imperfect foresight. We intertwine creative assemblages that shape the formation of knowledge-intensive activities at the operators’ level with scope of sectoral level interventions to underscore how the opportunities and constraints can enhance innovation for the common good. We use the case of digital data health regulatory agendas as illustration. We argue that this broader perspective on healthcare transformation is theoretically pertinent and practically useful, for management and policy.